http://bulletin.mfd.org.mk/volumes/Volume%2051/51_005.pdf - Tatjana Kadifkova Panovska; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2005)
The present study describes the ability of different extracts of H. plicatum obtained from flowers, stems and leaves, to act as natural antioxidants in different in vitro experimental models in which free radical reactions are involved: inhibition of DPPH (1,1-diphenyl-2- picrylhydrazyl) radical, inhibition of hydroxyl radicals and protection of β-carotene-linoleic acid model system. Investigate extracts showed radical scavenging activity with IC50 from 6 to 11 mg/ml. The extracts are capable to reacting with OH• radical with inhibition of its production ranged between 33-58%. The high preventive activity against the bleaching of beta-carotene (15-49% of initial value after 120 minutes) was also observed. The antioxidative activity of the extracts in the experimental systems was compared with that of reference substances: luteolin, quercetin, BHA, BHT and sylimarin (the main agent of the well-known milk thistle - Silybum marianum L.). Results of this study suggest that Helichrysum plicatum represent a natural source with antioxidant potential.